From the deep woods to civilization : chapters in the autobiography of an Indian - Eastman, Charles A., 1858-1939. (Boston : Little Brown, and Co., 1916)
From deep woods to civilization continues Eastman's captivating autobiographical work after Indian boyhood, telling the story of his years during school and into his life as a doctor. One of the highest educated Indians of his time, through his social work and his writings he was one of the best-known Indians of the early 20th century.
Foreword / E.G.E. -- The way opens -- My first school days -- On the White Man's trail -- College life in the West -- College life in the East -- A doctor among the Indians -- The Ghost Dance War -- War with the Politicians -- Civilization as preached and practised -- At the nation's capital -- Back to the woods -- The soul of the White Man.
Includes index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Eastman, Charles A., -- 1858-1939.; Eastman, Charles Alexander, -- 1858-1939.; Eastman, Charles A., -- 1858-1939; Santee Indians -- Biography; Santee Indians -- Biography; Santee -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Native American; Santee Indians; Autobiography; Biography; collective biographies; autobiographies (literary works); Autobiographies; Biographies; Autobiographies; Biographies; Autobiographies; Biographies